Quintessential Schwarzschild space-time - Villegas , Fulgencio (2021)
Recent discoveries determine that the universe is expanding rapidly. In order to explain this acceleration,a component of dark energy called quintessence has been proposed. In this article it is proposed tointroduce quintessence in Schwarzschild space-time. The Einstein eld equations for the Schwarzschilmetric are solved with an energy-moment tensor, whose components are the variables that dene thequintessence model.